Analysis of quantitative corporal variables for the determination of sexual dimorphism in the Paraguayan Avian Group named “Rustipollo” - Martínez-López, Roberto; Correa, Katiupcia; Centurión-Insaurralde, Liz Mariela (Revista Científica de la Facultad de Ciencias Veterinarias, 2022)
The study of quantitative body variables of animals, including morphometric variables, is an important auxiliary tool, since it contributes to the definition of the breed standard with scientific support according to updated identification models. In order to contribute with the aforementioned and in response to the need of producers to have chickens, which adapt to specific environments, in the Experimental Farm of the Faculty of Veterinary Sciences of the National University of Asunción, San Lorenzo- Paraguay, rustic chickens were raised, for dual purposes (meat and egg production). However, this avian group, called Rustipollo, has not yet been characterized. In this context, the objective was framed in the analysis of the most relevant quantitative body variables of this avian population: 80 Rustipollos, 25 males and 55 females were selected, by age group: Young, Adult and Senior. Fourteen characteristics were analyzed such as: beak length, crest length, neck length, back length, chest width, keel length, unfolded wing length, thigh length, tarsal length, middle finger length, body length, chin length and weight. The parameters that provided the most information about sexual dimorphism, in all the evaluated ages, were: chin length, crest length and wing length. While neck length, chest width, keel length, body length and thigh length, were indicators of sexual differentiation from week 48 onwards.